Civic oversight for MBG: Citizen Participation Monitors Child Nutrition - Zahira, Kyannissa Linggana; Aprilla, Amanda; Sugiono, Ladisha Putri; Sari, Yasmin Ambar; Supriyono, Supriyono (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
The Nutritional Meal Program (MBG) plays a vital role in improving the nutritional status of school children while requiring strong public accountability to ensure effective and transparent implementation. This study aims to develop a civic oversight model for MBG at the school level to strengthen program governance and enhance service quality. Using a rapid integrative literature review, the study analyzed various scientific sources, government policies, and credible reports. The findings identified five key pillars of community oversight: data transparency, application of simple HACCP-based food safety standards, responsive complaint mechanisms, cross-stakeholder collaboration, and participatory audits. Strengthening these pillars contributes to better information access, ensured food safety, and faster response to complaints in MBG implementation. The study recommends the use of public dashboards, easily applicable food safety SOPs, and accessible complaint channels for school communities and the wider public. The proposed civic oversight model is expected to enhance MBG accountability and increase public trust in the quality of school nutrition services, ultimately supporting the program’s effectiveness and sustainability.